Expansion of museums in Central Europe? - Jagodzińska, Katarzyna (RIHA Journal, 2015)
The paper presents reflections on the specificity of collections and museums of contemporary art in Central Europe and considers a possibility of creating a regional alternative for the West. The analysis is conducted in the context of the expansionist policy of contemporary museums – notably the Louvre, the Guggenheim Foundation, and the Hermitage – whose numerous new development projects gave rise to a number of dilemmas in the museological world. The author discusses global "museum brands" that invest in Central Europe and addresses the possible profits of the expansion of such "concerns" for culture in the region, as well as emphasises the potential of the region itself, which may be used for its development without the avail of the internationally renowned collectors' names.